Enhancement of Heat Transfer in Double Pipe Heat Exchanger. (2019) - Ponshanmugakumar, A.; Rajavel, R.
Abstract: The point of this present work is to improve warm execution attributes in a warmth exchanger tube by contemplating: (i) curved tapes in various courses of action; (ii) Cu-nanoparticles with various fixations as the working liquid. The tube embedded the turned tapes indicated prevalent warm execution consider when contrasted with plain tube due with persistent different whirling stream and multi-longitudinal vortices stream along the test tube. The higher number of curved tape embeds prompted an upgrade of warm execution that come about because of expanding contact surface territory, living arrangement time, whirl power and liquid blending with multi-longitudinal vortices stream. Additionally, game plan of contorted tapes in counter current was unrivaled vitality sparing gadgets for the commonsense utilize, especially at low Reynolds number. This was particularly the case for fourfold counter tapes in the cross bearings where warm exchange upgrade with generally low contact misfortune punishment was merited. . Utilizing water with Cu-nanoparticle as a working liquid yielded a higher warm execution than utilizing unadulterated water. It is watched that the most elevated general warmth exchange coefficient is accomplished by Cu nanofluids, which is 1705.686 W/m2K in 3% nanoparticle fixation at 5000 and 4000 Reynolds number for coolant and air individually contrasted with 992.649 W/m2K for the basefluid.